(untitled) (Global Journal of Science Frontier Research, 2020)
The article is an answer to the call of Dr. Stefano Veneroni, the Catholic University of the Sacred Heart explain the relationship between the continuum and discreteness in the epistemological model of the classical theory and explain how can Quantum Mechanics explain the connection between matter, antimatter, and gravitation, while being respectful of the (phoronomic) rules of general relativity? To answer the Dr. Stefano Veneroni questions, I first propose to recognize that Minkowski’s space-time, as well as an attempt Einstein in General Relativity Theory to generalize it to the case of accelerated motion, cannot be accepted as the basic model for describing the Universe. As such a basic model, the author sees the Finsler space of projective geometry, which allows combining the coordinate space and the space of impulses into a single continuum. In the article emphasized the role of the theory of global resonance in the birth of particles and the self-organization of matter in the five-dimensional continuum of the Universe.